Welfare implications of public expenditure in Indian agriculture: New evidence from CS-ARDL Approach - Akber, Nusrat; Kumar, Anjani (International Food Policy Research Institute, 2023)
This study explores the welfare implications of public expenditure at the subnational level. We empirically examine the efficiency of different categories of public expenditure on agriculture and irrigation using the novel cross-sectional autoregressive distributed lag (CS-ARDL) model and the data from 1981 to 2019 for 17 major agricultural states of India. The findings reveal the strong long-term positive effect in rural India of public sector expenditure on crop husbandry, agricultural research and education, soil and water conservation, irrigation, food storage and warehousing, animal husbandry and dairy development, and fisheries on total factor productivity (TFP), farm income, and poverty alleviation. Irrigation and electricity subsidies do not significantly affect outcome variables, while fertilizer subsidies showed a long-term negative impact on TFP, and credit subsidies had a positive effect on income and on the reduction of rural poverty. Other factors that were shown to have welfare implications included rainfall, literacy rate, and agricultural terms of trade (TOT), that is, the ratio of agriculture GDP to non-agriculture GDP. Policymakers should thus better target and rationalize government expenditure programs by removing unproductive input subsidies and reallocating those funds toward other types of public investment in Indian agriculture.